2019
DOI: 10.1002/gps.5138
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth and cognitive ability in late life: A systematic review

Abstract: Introduction Recent evidence suggests that growth restriction in utero may lead to neurocognitive disorders in late life, either through impaired brain development or adverse metabolic programming. Methods Systematic review of literature investigating the relationship between size at birth and cognitive abilities in late life. The search, data extraction, and rating for the quality of reporting were conducted independently by two researchers. Results Of 533 selected studies, 11 were included in this systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
9
0
3
Order By: Relevance
“…Findings from this study are consistent with some previous studies that have showed direct associations of birth weight with cognitive ability in childhood, adolescence, and young adulthood (Shenkin et al, 2004;Grove et al, 2017). The previous studies that have tested if body size at birth is associated with cognitive ability in late life have, however, produced contradictory findings (Grove et al, 2017;Krishna et al, 2019). Lower birth weight was associated with lower cognitive ability in three studies (Erickson et al, 2010;Costa et al, 2011;Raikkonen et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Findings from this study are consistent with some previous studies that have showed direct associations of birth weight with cognitive ability in childhood, adolescence, and young adulthood (Shenkin et al, 2004;Grove et al, 2017). The previous studies that have tested if body size at birth is associated with cognitive ability in late life have, however, produced contradictory findings (Grove et al, 2017;Krishna et al, 2019). Lower birth weight was associated with lower cognitive ability in three studies (Erickson et al, 2010;Costa et al, 2011;Raikkonen et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Direct comparisons of all measurements of size at birth with all reported cognitive outcomes in our study with those from the above-mentioned studies Birth size and cognition in late life 361 In this study, there was no evidence to support the DOHaD hypothesis that programming of cardiometabolic outcomes due to reduced prenatal growth and development had resulted in lower cognitive function in late life. None of the previously published twelve birth cohort studies (Krishna et al, 2019) were set up to explore the pathways of cognitive aging in a manner described in this study. However, similar to our study, the direct effects of birth size measures with late life cognition were independent of stroke and CHD (Raikkonen et al, 2013), diabetes and hypertension (Costa et al, 2011), and diabetes and CHD (Hyvarinen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] The majority of studies in the field have provided evidence for associations between early-life factors and cardiometabolic outcomes, [2,3] but the earlylife environment may also shape other health outcomes. [4][5][6] Currently, the mechanisms responsible for the observed relationships between early-life environment and later health outcomes are poorly understood. However, modulation of epigenetic marks, including DNA methylation, is a plausible mechanism mediating these relationships.…”
Section: Introductionmentioning
confidence: 99%